Triglyceride associated polymorphisms of the APOA5 gene have very different allele frequencies in Pune, India compared to Europeans - Chandak Giriraj R; Ward Kirsten J; Yajnik Chittaranjan S; Pandit Anand N; Bavdekar Ashish; Joglekar Charu V; Fall Caroline HD; Mohankrishna P; Wilkin Terence J; Metcalf Bradley S; Weedon Michael N; Frayling Timothy M; et al. (BMC, 2006)
Abstract Background The APOA5 gene variants, -1131T>C and S19W, are associated with altered triglyceride concentrations in studies of subjects of Caucasian and East Asian descent. There are few studies of these variants in South Asians. We investigated whether the two APOA5 variants also show similar association with various lipid parameters in Indian population as in the UK white subjects. Methods We genotyped 557 Indian adults from Pune, India, and 237 UK white adults for -1131T>C and S19W variants in the APOA5 gene, compared their allelic and genotype frequency and determined their association with fasting serum triglycerides, total cholesterol, HDL and LDL cholesterol levels using univariate general linear analysis. APOC3 SstI polymorphism was also analyzed in 175 Pune Indian subjects for analysis of linkage disequilibrium with the APOA5 variants. Results The APOA5 -1131C allele was more prevalent in Indians from Pune (Pune Indians) compared to UK white subjects (allele frequency 20% vs. 4%, p = 0.00001), whereas the 19W allele was less prevalent (3% vs. 6% p = 0.0015). Patterns of linkage disequilibrium between the two variants were similar between the two populations and confirmed that they occur on two different haplotypes. In Pune Indians, the presence of -1131C allele and the 19W allele was associated with a 19% and 15% increase respectively in triglyceride concentrations although only -1131C was significant (p = 0.0003). This effect size was similar to that seen in the UK white subjects. Analysis of the APOC3 SstI polymorphism in 175 Pune Indian subjects showed that this variant is not in appreciable linkage disequilibrium with the APOA5 -1131T>C variant (r2 = 0.07). Conclusion This is the first study to look at the role of APOA5 in Asian Indian subjects that reside in India. The -1131C allele is more prevalent and the 19W allele is less prevalent in Pune Indians compared to UK Caucasians. We confirm that the APOA5 variants are associated with triglyceride levels independent of ethnicity and that this association is similar in magnitude in Asian Indians and Caucasians. The -1131C allele is present in 36% of the Pune Indian population making it a powerful marker for looking at the role of elevated triglycerides in important conditions such as pancreatitis, diabetes and coronary heart disease.